Sunshine Vicram: A Good Day for Chardonnay - Book 2 - Jones, Darynda (New York, NY : St. Martin's Press, an imprint of St. Martin's Publishing Group, 2021)
"Running a small-town police force in the mountains of New Mexico should be a smooth, carefree kind of job. Sadly, full-time Sheriff--and even fuller-time coffee guzzler--Sunshine Vicram, didn't get that memo. All Sunshine really wants is one easy-going day. You know, the kind that starts with coffee and a donut (or three) and ends with take-out pizza and a glass of chardonnay (or seven). Turns out, that's about as easy as switching to decaf. (What kind of people do that? And who hurt them?) Before she can say iced mocha latte, Sunny's got a bar fight gone bad, a teenage daughter hunting a serial killer and, oh yes, the still unresolved mystery of her own abduction years prior. All evidence points to a local distiller, a dangerous bad boy named Levi Ravinder, but Sun knows he's not the villain of her story. Still, perhaps beneath it all, he possesses the keys to her disappearance. At the very least, beneath it all, he possesses a serious set of abs. She's seen it. Once. Accidentally. Between policing a town her hunky chief deputy calls four cents short of a nickel, that pesky crush she has on Levi which seems to grow exponentially every day, and an irascible raccoon that just doesn't know when to quit, Sunny's life is about to rocket to a whole new level of crazy. Yep, definitely a good day for chardonnay"--
Keywords: Sheriffs -- Fiction; Policewomen -- Fiction; Police -- Fiction. -- New Mexico; Small cities -- Fiction. -- New Mexico; Abduction -- Fiction; Criminal investigation -- Fiction; Murder -- Fiction. -- Investigation; Distillers -- Fiction; Man-woman relationships -- Fiction; Infatuation -- Fiction; New Mexico -- Fiction; Detective and mystery fiction; Humorous fiction; Thrillers (Fiction)